Clinicopathological and prognostic significance of Ras Association and Pleckstrin Homology domains 1 (RAPH1) in breast cancer - Kurozumi, Sasagu; Joseph, Chitra; Sonbul, Sultan; Aleskandarany, Mohammed A.; Pigera, Marian; Alsaleem, Mansour; Alsaeed, Sami; Kariri, Yousif; Nolan, Christopher C.; Diez-Rodriguez, Maria; Johnston, Simon; Mongan, Nigel P.; et al. (Springer, 2018)
BACKGROUND: Ras association and pleckstrin homology domains 1 (RAPH1) is involved in cytoskeleton regulation and re-epithelialisation in invasive carcinoma and therefore may play a key role in carcinogenesis and metastasis. We herein investigated the biological and clinical significance of RAPH1 in breast cancer using large annotated cohorts. METHODS: The clinicopathological and prognostic significance of RAPH1 was assessed at the genomic and transcriptomic levels using The Cancer Genome Atlas (TCGA) dataset (n=1039) and the results were validated using the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) cohort (n=1980). RAPH1 protein expression was evaluated by immunohistochemistry in a large, well-characterised cohort of early-stage breast cancer (n=1040). RESULTS: In both the TCGA-BRCA and METABRIC cohorts, RAPH1 mRNA expression and RAPH1 copy number alteration were strongly correlated. RAPH1 mRNA overexpression was significantly correlated with high expression of adhesion and EMT markers including CDH1, TGFbeta1 and CD44. RAPH1 mRNA overexpression was a significant predictor of a poor prognosis (Hazard ratio: 3.88; p = 0.049). High RAPH1 protein expression was associated with higher grade tumours with high proliferation index, triple negative phenotype and high E-cadherin expression. High RAPH1 protein expression was an independent predictor of shorter survival (Hazard ratio: 4.37; p = 0.037). CONCLUSIONS: High RAPH1 expression is correlated with aggressive breast cancer phenotypes and provides independent prognostic value in invasive breast cancer.